Pengaruh Katalis Terhadap Rendemen Reaksi Transesterifikasi - Br Tarigan, Romi Yana Widiawati; Gugule, Sanusi; Tuerah, Jeanne Maria; Maanari, Chaleb (Jurnal Kimia Fullerene, 2023)
Research has been carried out on the effect of a catalyst on the yield of transesterification reactions. Pure coconut oil is made mechanically without heating using fresh coconut meat or what is called non-copra, followed by a base-catalyzed transesterification reaction using KOH and NaOH. The purpose of this study was to determine the effect of the catalyst on the yield of the transesterification reaction. The results of the reaction were analyzed by determining the physico-chemical properties and analysis of Gas Chromatography-Mass Spectrometry (GC-SM). The results showed that the average reaction yield with KOH catalyst was 74.3% and 70% NaOH catalyst. The most dominant GC-SM identification results were ethyl caproate 4.12%, ethyl capricate 4.99%, ethyl laurate 54.97%, ethyl myristate 18.49%, ethyl palmitate 8.13%, 9.12 octadecatrin-1-ol 5.24% and ethyl strearate 2.28%.